KAJIAN PEMASARAN IKAN TOMAN (Channa micropeltes) DI KECAMATAN DANAU PANGGANG KABUPATEN HULU SUNGAI UTARA PROVINSI KALIMANTAN SELATAN - Emmy Lilimantik; Tri Dekayanti; Alista Alista (Universitas Lambung Mangkurat, 2023)
This study aims to examine the market for snakehead fish (Channa micropeltes) in Danau Panggang District, Hulu Sungai Utara Regency, South Kalimantan Province. The data used are primary and secondary data, while data collection used with the methods of observation, interviews and documentation. Simple random sampling method are used to collect the fish farmers sampling and the snowball sampling method to samples the marketing of institutions. The data analysis used includes (a) marketing channel analysis, (b) marketing margin analysis and (c) farmer's share analysis. The results of the analysis explain that (a) the marketing channel consists of 2 channel patterns, namely in the first channel marketing begins with the presence of several fish farmers who sell snakehead fish to wholesaler and then sells to retailers for distribution to final consumers and in the second channel shows the that some of the fish farmers sell snakehead fish to wholesaler to be sell to final consumers, (b) the value of the marketing margin in the first channel is IDR 7,850 and in the second channel is IDR 5,850. (c) the value of farmer's share in the first channel is 79% and in the second channel is 83%.